EFEKTIVITAS TEKNIK RELAKSASI NAPAS DALAM DAN MOBILISASI DINI TERHADAP TINGKAT NYERI PADA PASIEN POST OPERASI SECTIO CAESAREA DI RUMAH SAKIT MURNI TEGUH ROSIVA MEDAN - Marpaung, Eny Novita; Simatupang, Lenny Lusia (STIKes Mitra Husada Medan, 2024)
Background: Caesarean section (CS) is another way for women to choose the delivery process in addition to medical and non-medical indications. The side effect of CS surgery is pain in the incision. Non-pharmacological actions that are thought to be able to reduce pain intensity are deep breathing relaxation and early mobilization, but it is not yet known which of these two actions is more effective in reducing pain. Objective: To determine the effect of deep breathing relaxation techniques and early mobilization on pain levels in post-cesarean section patients. Method: Quantitative research with a quasi-experimental approach and a two-group pre and post test design without a control group. The study was conducted at RSIA Murni Teguh Rosiva Medan. The population size was 47 patients per month and the sample size was 42 people divided into 2 groups, each group consisting of 21 people. Sampling was by accidental sampling. Analysis was carried out univariately in the frequency distribution table and bivariately using the Independent Sample T-Test because the data were normally distributed. Results: The study showed that in post-cesarean section patients, deep breathing relaxation techniques resulted in a more significant decrease in pain levels compared to early mobilization, with an average posttest pain value of 1.86 ± 0.964 (mild pain) and 3.62 ± 1.024 (moderate pain), respectively. The difference in pain between the two groups was significant with a p value = 0.000, which means p <0.05. Conclusion: Deep breathing relaxation techniques are more effective in reducing pain levels in post-cesarean section patients than early mobilization. Suggestion: It is recommended that further researchers conduct further research on how to overcome post-operative pain using other complementary therapies such as warm/cold compresses, aromatherapy, and others.